Educational Needs assessment (and Exposure Rate) of Emergency Medicine Technicians - One Step toward Accountable Education - farzaneh zarei; ghobad moradi; reza pira (مجله علمی دانشگاه علوم پزشکی کردستان)
Background and Aim: A realistic assessment of society's needs and the needs of targeted learners as the main audience are essential. This study was conducted to determine the educational needs of emergency medicine technicians (common and important signs, symptoms, and diseases) to be used in the revision of the curriculum based on accountability. Materials and Methods: This was a cross-sectional study. The research population was all emergency medical technicians working in Kurdistan province. The research tool was a questionnaire made by the researcher, whose content validity (CVR=0.85, CVI=0.92) and reliability (0.97) indices were calculated, and descriptive statistical methods (frequency, ratio, mean, and standard deviation) were used for data analysis. Results: In this study, 366 questionnaires were analyzed. All subjects were male. The highest exposure to hypertension (4.34±0.79) and the highest need for education was about MI (myocardial infarction) (3.71±1.21). Also, regarding the signs and symptoms, the most exposure was related to hypertension (4.52±0.77), Respiratory distress (4.42±0.78), and chest pain (4.40±0.87), and the most need for education was related to convulsions (3.41±1.21) and hemiplegia (3.40±1.20) and tracheal deviation (3.38±1.23). Conclusion: Considering that to determine the educational priorities, the level of exposure and the level of need for education are considered (which are the criteria for determining the necessity of learning) and on the other hand, the headings of the educational curriculum of pre-hospital emergency medicine are also extensive, it seems that it is necessary to carry out wider studies in this context.